ANALISA MODIFIKASI MODEL BODY KENDARAAN OBHI-MEC UNUD TERHADAP KOEFISIEN DRAG MENGGUNAKAN ANSYS FLUENT - Simanjuntak, Endy Josua; Karohika, I Made Gatot; Widiyarta, I Made (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract In the development of a transportation technology, efforts have been made to increase vehicle efficiency by optimizing aerodynamic aspects. In the automotive field, aerodynamics has a huge role in determining vehicle body design. This research was carried out by simulating and analyzing the Obhi-Mec Unud bio-hybrid vehicle body model using ANSYS Fluent to see the effect of vehicle body modifications on the drag coefficient, lift coefficient, and the shape of the air flow pattern on the surface of this vehicle body. The design before modification provides a smaller drag coefficient value, while the design after modification provides a smaller lift coefficient value. Increasing vehicle speed will increase the drag coefficient value. However, increasing vehicle speed will produce different airflow patterns in each body design. Keywords: Drag Coefficient, Lift Coefficient, Airflow Patterns, Aerodynamics, Computational Fluid Dynamics